Model Pembelajaran Menyimak Kritis Melalui Media Interaktif pada Mahasiswa Tadris Bahasa Indonesia IAIN Madura - Ayuanita, Kristanti; Hafid Effendy, Moh. (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research is motivated by a problem when after listening activities there are only 4-5 students who are actively discussing. And the others are silent not expressing their opinions. The listening process requires serious attention from students. So the need for learning models that are applied by lecturers to innovative students in order to change learning patterns for the better. This research used descriptive qualitative. The results showed that the lecturer used all media in the laboratory, especially audio-visual media that could be used interactively. In addition, interactive media is an audio visual media that is used by lecturers as a tool in delivering critical listening skills learning material. In this case the lecturer uses a computer, a projector, a set of multimedia complete with a headset in each chair. Audio visual media was chosen from internet sources such as on YouTube in the form of recorded material that was chosen in such a way as to help the process of listening critically to make it easier for Indonesian Tadris IAIN Madura students to understand. On the other hand, students find it helpful to listen by using interactive media. Instead they feel bored when learning listening skills are only filled with discussion or lecture methods. They lack concentration and are sometimes easily drowsy. The supporting factors in learning listening skills are conducive classroom conditions coupled with multimedia which helps the process of teaching and learning critical listening skills.